From screen to speech: Multimodal learning in EFL speaking classrooms - Rozi, Choirul; Munir, Ahmad; Suhartono, Suhartono; Fauziah, Humairah (Edelweiss Applied Science and Technology, 2025)
This study explores the effectiveness of video-project assignments (VPAs) combined with a multimodal teaching approach to enhance speaking proficiency in English as a Foreign Language (EFL) classrooms. The objective was to move beyond conventional video production tasks by integrating listening, reading, and writing skills into the speaking curriculum. A pre-experimental design was employed with 31 undergraduate students enrolled in a speaking course at a university in East Java, Indonesia. Data were collected through pre- and post-test speaking assessments and a questionnaire on students’ perceptions. The results of the paired-sample t-test showed a significant improvement in students’ speaking performance after the intervention. Questionnaire findings further revealed that students perceived VPAs as engaging, collaborative, and beneficial for developing confidence and fluency, with peer feedback recognized as particularly valuable. The study concludes that multimodal teaching through VPAs not only supports measurable gains in speaking proficiency but also fosters learner motivation and positive attitudes toward collaborative language practice. These findings imply that integrating multimodal strategies into speaking instruction can provide more meaningful learning opportunities and inform future curriculum design.